A comprehensive study of the elasto-plastic contact of a sphere and a flat. (January 2016) - Ghaednia, Hamid; Pope, Sara A.; Jackson, Robert L.; Marghitu, Dan B.
Abstract: In this paper the frictionless contact of an elasto-plastic sphere with an elasto-plastic flat has been studied. Previously, elasto-plastic contact has been studied mostly for either the isolated flattening or indentation cases. This work analyzes the case in between these, where both surfaces deform elasto-plastically. It has been shown that the deformation on both objects has a significant effect on the real area of contact and the contact force. The ratio between the yield strengths of the sphere and the flat has been defined as a major governing factor. FEM analysis has been performed for more than 400 cases, and a comprehensive formulation has been developed based on the FEM results in order to predict the contact parameters. Abstract : Highlights: The contact of an elasto-plastic sphere with an elasto-plastic flat has been studied. The effect of deformation on both of the objects has been analyzed. A new parameter, S y ⁎, has been defined as an important factor in contact problems. More than 400 different finite element cases have been performed. Empirical formulation has been provided to predict the contact parameters.